Organizational communication between teachers and managers: comparative analysis of Colombian institutions (2020)
The objective of this research is to determine the relevant factors of communication problems in two official schools in Colombia. The sample consisted of 58 teachers, who completed a 9-question survey. The data analysis describes the internal communication factors and then develops the comparative analysis using the U-Mann Whitney test. Despite sharing similar characteristics of official schools according to the Ministry of National Education, it is revealed that both institutions have significant differences in their internal organizational communication. key words: internal organizational communication, educational institutions, official schools, comparative analysis